Response Evaluation and Survival Prediction Following PD‐1 Inhibitor in Patients With Advanced Hepatocellular Carcinoma: Comparison of the RECIST 1.1, iRECIST, and mRECIST Criteria - Zhou, Meng; Zhang, Chunhui; Nie, Jianhua; Sun, Yajuan; Xu, Ye; Wu, Fangfang; Huang, Yuhong; Li, Shun; Wang, Yuan; Zhou, Yang; Zheng, Tongsen (Frontiers in oncology, 2021)
Precise evaluation of the efficacy of immunotherapy is critical in the effective management and treatment of advanced hepatocellular carcinoma (HCC). Therefore, the purpose of this study was to compare the response assessments achieved by different criteria and to evaluate the correlation between survival outcome and response assessment in HCC treated with programmed cell death protein 1 (PD-1) inhibitor. Fifty patients with advanced HCC treated with first-line PD-1 inhibitor with baseline and follow-up CT images were analyzed. The patients were categorized into responders and nonresponders according to the criteria. When the response assessments between RECIST 1.1 and mRECIST were compared, no statistically significant differences were observed. Overall response rate was 16% by RECIST 1.1 and iRECIST and was 24% by mRECIST. According to RECIST 1.1 and mRECIST, overall survival (OS) and progression-free survival (PFS) were not statistically different between the complete response (CR) and partial response (PR) groups and the stable disease (SD) and progressive disease (PD) groups. The OS and PFS were significantly different between responders and nonresponders according to mRECIST. The Cohen's Kappa for RECIST 1.1, iRECIST, and mRECIST was 0.534, 0.438, and 0.363, respectively. The mRECIST criteria have a powerful ability to discriminate between responders and nonresponders and demonstrated significantly longer OS and PFS in responders than in nonresponders. However, mRECIST needs to be further improved in order for it to be widely used in the clinical evaluation of immunotherapy in HCC.